Guidelines for Perioperative Care in Cytoreductive Surgery (CRS) with or without hyperthermic IntraPEritoneal chemotherapy (HIPEC): Enhanced recovery after surgery (ERAS®) Society Recommendations — Part I: Preoperative and intraoperative management. Issue 12 (December 2020) - Hübner, Martin; Kusamura, Shigeki; Villeneuve, Laurent; Al-Niaimi, Ahmed; Alyami, Mohammad; Balonov, Konstantin; Bell, John; Bristow, Robert; Guiral, Delia Cortés; Fagotti, Anna; Falcão, Luiz Fernando R.; Glehen, Olivier; et al.
Abstract: Background: Enhanced recovery after surgery (ERAS) pathways have been shown to considerably reduce complications, length of stay and costs after most of surgical procedures by standardised application of best evidence-based perioperative care. The aim was to elaborate dedicated recommendations for cytoreductive surgery (CRS) ± hyperthermic intraperitoneal chemotherapy (HIPEC) in a two-part series of guidelines based on expert consensus. The present part I of the guidelines highlights preoperative and intraoperative management. Methods: The core group assembled a multidisciplinary panel of 24 experts involved in peritoneal surface malignancy surgery representing the fields of general surgery (n = 12), gynaecological surgery (n = 6), and anaesthesia (n = 6). Experts systematically reviewed and summarized the available evidence on 72 identified perioperative care items, following the GRADE (grading of recommendations, assessment, development, evaluation) system. Final consensus (defined as ≥50%, or ≥70% of weak/strong recommendations combined) was reached by a standardised 2-round Delphi process, regarding the strength of recommendations. Results: Response rates were 100% for both Delphi rounds. Quality of evidence was evaluated high, moderate low and very low, for 15 (21%), 26 (36%), 29 (40%) and 2 items, respectively. Consensus was reached for 71/72(98.6%) items. Strong recommendations were defined for 37 items, No consensus could be reached regarding the preemptive use of fresh frozen plasma. Conclusion: The present ERAS recommendations for CRS±HIPEC are based on a standardised expert consensus process providing clinicians with valuable guidance. There is an urgent need to produce high quality studies for CRS±HIPEC and to prospectively evaluate recommendations in clinical practice.